Comparative Financial Performance of Digital Banks Using CAMEL Model : Evidence from the Indonesia Digital Banking Industry - Hendi Yudhanto Adinugroho; Dwi Winarno; Rian Sofiyan (Universitas Muhammadiyah Surakarta, 2026)
This study aims to evaluate and compare the financial performance of leading digital banks in Indonesia PT Bank Jago Tbk, PT Bank Neo Commerce Tbk, and PT Allo Bank Indonesia Tbk during the period of 2021–2024. Amidst the rapid digital transformation and shifting consumer behavior in Indonesia's financial sector, assessing the stability and sustainability of technology driven institutions is essential. Using a descriptive-comparative quantitative approach, this research employs the CAMEL framework, focusing on key financial ratios: Capital Adequacy Ratio, Non Performing Loan, Operating Expenses to Operating Income, Return on Equity, and Loan to Deposit Ratio. Data analyzed using descriptive statistics and ANOVA to identify significant performance differences. The results indicate that while all three banks maintained capital adequacy well above regulatory requirements, significant variances exist in efficiency and profitability. Allo Bank demonstrated superior operational efficiency and the highest profitability, while Bank Neo Commerce faced initial profitability challenges before recovering in 2024. Bank Jago showed a stable transition from aggressive expansion to improved credit quality. Statistical tests confirm significant differences in financial health across the sampled banks. These findings provide valuable insights for regulators in monitoring digital banking stability and for management in optimizing risk based digital business models.